The Effect Of Corporate Social Responsibility Disclosure On Tax Planning With Firm Size As A Moderating Variable: Case Study of the Food and Beverage Sub-sector Listed on the Indonesia Stock Exchange for the Period 2020-2024 - Nurhayati Tambun; Anissa Yuniar Larasati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study tries to find out if corporate social responsibility (CSR) has an impact on tax planning, with the size of the company acting as a factor that could influence this relationship. The research is based on quantitative methods and uses secondary data from financial reports and sustainability reports. The focus is on companies in the food and beverage sector that are listed on the Indonesia Stock Exchange between 2020 and 2024. To collect data, purposive sampling was used, which included companies that were listed on the IDX during that time, had inconsistent financial reporting, experienced losses, had inconsistent sustainability reporting, or did not use the GRI index. The final sample included 10 companies, providing a total of 50 data points. The data was analyzed using SPSS with a technique called moderated regression analysis (MRA). The findings showed that CSR does not influence tax planning, and the company size did not act as a moderator in this relationship.